2003
DOI: 10.1590/s1415-47572003000400005
|View full text |Cite
|
Sign up to set email alerts
|

Studies of blood groups and protein polymorphisms in the Brazilian horse breeds Mangalarga Marchador and Mangalarga (Equus caballus)

Abstract: Allelic frequencies at 12 loci (five blood groups: C, D, K, P, and U; and seven protein polymorphisms: Al, A1B, Es, Gc, Hb, PGD, and Tf), are given for two Brazilian horse breeds: Mangalarga Marchador and Mangalarga. The high genetic identity value found (96.0%) is consistent with their common origin, although, at some point of the development of Mangalarga Marchador, Mangalarga separated from the original stock. The expected average heterozygosity was higher in Mangalarga Marchador. The populations presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
(7 reference statements)
0
6
3
Order By: Relevance
“…The F ST , in our case, ranged from 2.6 to 8.5 % with an average of 5.5 % (0.4). These levels for the F ST in Tunisian horse breeds are smaller than those previously found in Algerian breeds (F ST = 8.6 %, Berber et al, 2014), Polish breeds (F ST = 10 %, Zabek et al, 2005), Brazilian breeds (F ST = 11.7 %; Lippi and Mortari, 2003). However, they are slightly lower than the 6.5 % reported by Behl et al (2007) for five Indian horse breeds.…”
Section: Genetic Diversity Within and Among Breedscontrasting
confidence: 50%
“…The F ST , in our case, ranged from 2.6 to 8.5 % with an average of 5.5 % (0.4). These levels for the F ST in Tunisian horse breeds are smaller than those previously found in Algerian breeds (F ST = 8.6 %, Berber et al, 2014), Polish breeds (F ST = 10 %, Zabek et al, 2005), Brazilian breeds (F ST = 11.7 %; Lippi and Mortari, 2003). However, they are slightly lower than the 6.5 % reported by Behl et al (2007) for five Indian horse breeds.…”
Section: Genetic Diversity Within and Among Breedscontrasting
confidence: 50%
“…However, our F ST value was slightly smaller than that found in some other studies, such as the 10% reported by Zabek et al (2005) for some Polish breeds (Bilgoraj, Malopolski and Thoroughbreds), the 10.9% reported by Díaz et al, (2002) for the Argentine Creole and Thoroughbreds and the 11.7% reported by Lippi and Mortari (2003) for two Brazilian breeds (Mangalarga Marchador and Mangalarga). It has been pointed out by some authors that the typical high within-population variability of microsatellites may result in low differentiation values (Hedrick, 1999;Balloux and Lugon-Moulin, 2002).…”
Section: Discussioncontrasting
confidence: 82%
“…The genetic differentiation value (F ST ) was higher than that observed in four Basque-Navarrese semi-feral breeds (Solis et al, 2005) and lower than those obtained in European (Zabek et al, 2005;Azor et al, 2007) and South American breeds (Lippi and Mortari, 2003). On average, a deficit of heterozygotes of 2.3% (F IS ) exists for each analysed breed; this deficit was 8.3% in the whole sample (F IT ) ( Table 1).…”
Section: Discussionmentioning
confidence: 68%